Air quality accountability: Developing long-term daily time series of pollutant changes and uncertainties in Atlanta, Georgia resulting from the 1990 Clean Air Act Amendments. (February 2019) - Henneman, Lucas R.F.; Liu, Cong; Chang, Howard; Mulholland, James; Tolbert, Paige; Russell, Armistead
Abstract: The 1990 Clean Air Act Amendments codified major institutional changes relating to the management of air pollutants in the United States. Recent research years has attributed reduced emissions over the past two decades to regulations enacted under these Amendments, but none have separated long-term daily impacts of individual regulatory programs on multiple source categories under a consistent framework. Using daily emissions and air quality measurements along with a detailed review of national and local regulations promulgated after the Amendments, we quantify daily changes in emissions and air quality attributable to regulations on electricity generating units and on-road mobile sources. To quantify daily changes, we develop nine sets of counterfactual emissions and ambient air pollution concentration time series for 10 pollutants that assume individual regulatory programs and combinations thereof were not implemented. In addition to daily impacts, we estimate uncertainties in these results. These counterfactual daily ambient concentrations reveal high seasonality and increasing effectiveness of most regulations between 1999 and 2013. Monthly average counterfactual concentrations in scenarios that assume no new regulations on electricity generating units and mobile sources are greater than observed concentrations for all pollutants except ozone, which has seen increased wintertime concentrations accompany summertime decreases. By the end of the period, electricity generating unit emissions reductions under the Acid Rain Program and Clean Air Interstate Rule and their respective related local programs led to similar PM2.5 concentration decreases. Of the mobile source regulations, rules on gasoline and diesel vehicles led to similar reductions in annual PM2.5, and gasoline programs led to double the summertime ozone reductions as diesel programs. The nine sets of daily time series and their uncertainties were designed for use in air pollution accountability health studies. Highlights: Attribution of emissions and air quality changes to national and local regulations Daily counterfactual emissions and air quality time series and uncertainties Regulatory impacts differ by source, season, and pollutant.